Mengkaji Sepercik Ajaran Agama Buddha dalam Kitab Primbon Atassadhur Adammakna - Arif Muzayin Shofwan (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
Buddhism is a religion that has developed in Indonesia (the archipelago) for quite a long time and has become a guide for people's lives, so that sparks of its teachings can be found in several ancient texts and primbon. This qualitative research using literature study will examine a glimpse of Buddhist teachings contained in the Primbon Atassadhur Adam Book, the meaning of the legacy of Kanjeng Pangeran Harya Cakraningrat, Raden Ngabehi Kartohasmoro, and Raden Soemodidjodjo and compiled by RW. Sumbaga. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research produces the following three conclusions. Firstly, the spark of Buddhist teachings in the primbon book is quoted from the Anguttara Nikaya Book on the opening page as a basis for spiritual practitioners who wish to practice prayers, chant mantras and inner (spiritual) practices through the primbon book. Second, the spark of Buddhist teachings can be intended so that spiritual practitioners through the primbon book can obtain the true truth in accordance with the correct understanding and thoughts. If someone has obtained the true truth in accordance with the correct understanding and thoughts, then he will have broad and deep insight when understanding life which is full of diversity.